2017
DOI: 10.1186/s12933-017-0631-6
|View full text |Cite
|
Sign up to set email alerts
|

Transcatheter aortic valve implantation and surgical aortic valve replacement among hospitalized patients with and without type 2 diabetes mellitus in Spain (2014–2015)

Abstract: BackgroundType 2 diabetes mellitus (T2DM) is strongly related to the in-hospital and short-term prognosis in patients with cardiovascular diseases needing surgical or invasive interventions. How T2DM might influence the treatment of aortic stenosis (AS) has not been completely elucidated for surgical aortic valve replacement (SAVR) or transcatheter aortic valve implantation (TAVI). The aims of this study were: (1) to describe the use of aortic valve replacement procedures (TAVI and SAVR) among hospitalized pat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
22
0

Year Published

2018
2018
2020
2020

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 26 publications
(24 citation statements)
references
References 34 publications
2
22
0
Order By: Relevance
“…This is consistent with the findings of some studies (https://apurologia.pt/. A, 2008;Wilke et al, 2015;Hirji et al, 2012;Mazzi et al, 2017;de Decker et al, 2017;Mendez-Bailon et al, 2017;Rodríguez-Acelas et al, 2017;Shwartz et al, 1994) that have reported a high number of unnecessary hospitalizations. One study (Rosenthal et al, 2014) showed that marked differences exist in the use of medical resources, hospital beds, diagnostic exams, and medical treatments putting the patient at risk of infection.…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…This is consistent with the findings of some studies (https://apurologia.pt/. A, 2008;Wilke et al, 2015;Hirji et al, 2012;Mazzi et al, 2017;de Decker et al, 2017;Mendez-Bailon et al, 2017;Rodríguez-Acelas et al, 2017;Shwartz et al, 1994) that have reported a high number of unnecessary hospitalizations. One study (Rosenthal et al, 2014) showed that marked differences exist in the use of medical resources, hospital beds, diagnostic exams, and medical treatments putting the patient at risk of infection.…”
Section: Discussionsupporting
confidence: 91%
“…Another study (de Decker et al, 2017) found that a high burden of comorbidities (stroke, heart failure, myocardial infarction, and functional cognitive impairment) increased the risk of hypoglycemic events in elderly patients (aged over 80 years) with diabetes. Mendez-Bailon et al (2017) studied 715 patients with diabetes admitted for cardiovascular diseases who underwent invasive cardiac procedures, and found that obesity (18%), arterial hypertension (67.3%), lipid abnormalities (45.8%), renal failure (14.07%), and intermittent claudication (1.65%) were risk factors for adverse events during hospitalization.…”
Section: Introductionmentioning
confidence: 99%
“…The results of the Virginia Cardiac Services Quality Initiative database showed that the prevalence of diabetes in 2002–2008 was 30.0%, 33.0% in 2009–2011 and 36.7% in 2012–2015 (p < 0.01) [ 24 ]. The expected aging of the Spanish population will surely result in an increase in the prevalence of T2DM patients among those undergoing SAVR in the next decade [ 14 ].…”
Section: Discussionmentioning
confidence: 99%
“…Several studies have assessed the impact of diabetes on the outcomes of SAVR and concluded that T2DM is one of the predictors of poor outcomes after SAVR [ 12 , 13 ]. Studies conducted in Spain and other countries have found that T2DM diabetic patients with aortic stenosis undergoing a valvular replacement procedure through SAVR or TAVR did not have higher mortality or complication rates than nondiabetic patients during hospitalization [ 14 , 15 ].…”
Section: Introductionmentioning
confidence: 99%
“…In fact, aortic valve replacement is the second most common cardiac procedure currently performed. Between 2014 and 2015, 18,000 of these operations were performed solely in Spain [3]. Research aimed at uncovering the pathological mechanisms behind aortic valve stenosis is, for these reasons, of vital necessity.…”
Section: Introductionmentioning
confidence: 99%